Alterations in gut microbiota and plasma metabolites in pulmonary arterial hypertension secondary to congenital left-to-right shunt heart disease: potential mechanisms and biomarkers - Li, Diwen; Zhao, Tianli; Gong, Xueyang; Ahemaiti, Yiliya; Wei, Luyao; Huang, Yuyang; Hu, Shijun (Frontiers in Genetics, 2026)
IntroductionPulmonary arterial hypertension (PAH) secondary to congenital left-to-right shunt heart disease (CL-RSHD) is a life-threatening complication with unclear microbial and metabolic mechanisms. This study investigated gut microbiota and plasma metabolic alterations in CL-RSHD-associated PAH to identify biomarkers and mechanistic pathways.MethodsThis cross-sectional study included 86 participants: healthy controls (HC, n = 13), CL-RSHD (n = 46), and CL-RSHD + PAH (n = 27). Gut microbiota was analyzed using 16S rRNA gene sequencing of the V3–V4 region on 41 fecal samples (HC, n = 9; CL-RSHD, n = 15; and CL-RSHD + PAH, n = 17). Untargeted plasma metabolomics was analyzed on all 86 plasma samples. Microbial diversity, differential taxa (DESeq2), metabolic pathways (OPLS-DA, KEGG), and biomarker potential (ROC curves) were assessed. Dynamic correlations linked microbiota-metabolite interactions.ResultsCL-RSHD + PAH patients showed preserved α/β-diversity but distinct taxonomic shifts: enriched Lachnoclostridium phocaeense (Firmicutes) and reduced SCFA-producing Anaerostipes. Metabolomics revealed dysregulated steroid biosynthesis, cortisol metabolism, and oxidative stress pathways. Key metabolites, including elevated 5-hydroxymethylcytidine (5-hmC) and γ-L-glutamyl-L-cysteine, and reduced histidine intermediate D-E1IG3P, correlated with PAH severity. Strong microbiota-metabolite interactions (e.g., Lactonifactor-D-E1IG3P, r = 0.82, P < 0.01) suggested a disrupted vascular remodeling axis. Metabolites like ADP-glucose (AUC = 0.94) and 3-phenylpropyl glucosinolate (AUC = 0.92) showed high diagnostic accuracy.ConclusionCL-RSHD-associated PAH involves gut microbial restructuring and metabolic reprogramming linked to immune-inflammatory activation and oxidative stress. The Firmicutes-histidine metabolism axis emerges as a therapeutic target. Despite limitations, this study provides foundational insights into microbial-metabolic drivers of PAH, highlighting novel biomarkers for early diagnosis and intervention.